Lexical Density and Cohesion in Modern Standard Arabic Essays Written by Foreign Learners - Al-Khaldi; Omair Benyoussef (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the lexical density and cohesion features in Modern Standard Arabic (MSA) essays written by foreign learners, with the aim of identifying key patterns that characterize learner language production. Using a mixed-method approach, the research analyzes 80 essays from intermediate and advanced learners enrolled in Arabic language programs. Quantitative measures of lexical density were calculated to determine the proportion of content words, while qualitative and quantitative analyses of cohesive devices examined the frequency and appropriateness of reference, conjunctions, lexical ties, and substitution mechanisms. The findings reveal that learners at both levels tend to rely heavily on basic lexical items, resulting in moderate lexical density, but advanced learners demonstrate greater variation and structural complexity. Cohesion analysis shows frequent use of additive and causal conjunctions, though misuse of reference and lexical repetition remains common, indicating limited control of cohesive harmony. These results highlight the developmental nature of foreign learners’ interlanguage in MSA writing and underscore the need for pedagogical interventions focusing on vocabulary expansion and cohesive device instruction. The study contributes to a deeper understanding of Arabic learner corpora and offers implications for curriculum design, assessment, and instructional strategies in teaching MSA writing skills.